Larvicidal efficacy and biological stability of a botanical natural product, zedoary oil-impregnated sand granules, against Aedes aegypti (Diptera, Culicidae) - Champakaew D. (2014)
Chemical analysis on Curcuma zedoaria rhizome volatile oil, using gas chromatography-mass spectrometer techniques, demonstrated the presence of β-tumerone (19.88%), 1,8-cineole (8.93%), and 7-zingiberene (7.84%) as major constituents. Larvicidal efficacy against Aedes aegypti mosquitoes of zedoary oil and its formulated preparation, zedoary oil-impregnated sand granules, were investigated and compared with that of Abate®sand (temephos). Zedoary oil exhibited pronounced potential against the fourth instar larvae of A. aegypti with an LC50 and LC99 of 33.45 and 83.39 ppm, respectively. Application of zedoary oil at a dosage yielding ten times that of LC99 offered complete larval mortality (100% mortality) for a period of 3 days, and the larval mortality subsequently decreased to lower than 50% after application for more than 5 days. Zedoary oil-impregnated sand granules provided remarkably longer activity, with a larval mortality of 100% for a period of 9 days; and mortality below 50% was obtained in week 3 of application. The complete larval mortality that resulted from applying temephos at dosages of 0.1 and 1 ppm persisted for a period of 6 days and 4 weeks, respectively, and the larval mortality below 50% was reported on day 18 and week 11, respectively. Testing A. aegypti species against stored samples of zedoary oil-impregnated sand granules demonstrated that the product stored at 4°C showed the longest larvicidal activity, followed by those kept at ambient temperature and 45°C, yielding a complete larval mortality for 9, 8, and 6 days, respectively. Most samples of zedoary oil-impregnated sand granules stored at each temperature for 1 month showed slightly higher efficacy than those kept for 2 months. The larvicidal efficacy of samples stored at 4°C seemed to be comparable to that of the fresh sample. The efficacy in killing A. aegypti larvae and good biological stability of zedoary oil-impregnated sand granules make this product promising as an alternative to essential oil in the development of new botanical natural larvicide for use in mosquito control programs. © 2006 Springer-Verlag.